2015
DOI: 10.1590/1983-084x/15_003
|View full text |Cite
|
Sign up to set email alerts
|

Potencial inseticida de óleos essenciais sobre Tribolium castaneum em milho armazenado

Abstract: RESUMO:O presente trabalho teve como objetivo investigar o potencial inseticida de óleos essenciais de Croton heliotropiifolius, Croton pulegiodorus, Myracrodruon urundeuva e Ocimum basilicum sobre adultos de Tribolium castaneum em milho armazenado. Para cada óleo foram realizados bioensaios de fumigação, repelência e o efeito sobre a taxa instantânea de crescimento (r i ), em cinco concentrações (0; 5; 10; 15 e 20 μL). Os bioensaios foram conduzidos sob condições constantes de temperatura (28±2 ºC), umidade r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
0
8
0
8
Order By: Relevance
“…Brito et al (2015) evaluated essential oils of Croton heliotropiifolius Kunth (Euphorbiaceae), C. pulegiodorus, and Myracrodruon urundeuva Allemão (Anacardiaceae) on coleoptera pests of stored common bean and found a reduction in adult emergence through ovicidal/larvicidal effect. Similarly, Magalhães et al (2015) reported that essential oils of C. pulegiodorus and C. heliotropiifolius caused 100% reduction in emergence of T. castaneum in stored maize.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Brito et al (2015) evaluated essential oils of Croton heliotropiifolius Kunth (Euphorbiaceae), C. pulegiodorus, and Myracrodruon urundeuva Allemão (Anacardiaceae) on coleoptera pests of stored common bean and found a reduction in adult emergence through ovicidal/larvicidal effect. Similarly, Magalhães et al (2015) reported that essential oils of C. pulegiodorus and C. heliotropiifolius caused 100% reduction in emergence of T. castaneum in stored maize.…”
Section: Resultsmentioning
confidence: 90%
“…Studies have shown the potential of using essential oils as an alternative method for seed protection and control of several pests of stored products in Brazil (COITINHO et al, 2011;BRITO et al, 2015;MAGALHÃES et al, 2015;SOUZA et al, 2016;ARAÚJO et al, 2017). Essential oils present different effects on insects (SUTHISUT; FIELDS; CHANDRAPATYA, 2011; KŁYS; MALEJKY; NOWAK-CHMURA, 2017), causing biochemical, physiological, and behavioral disorders that lead to their death or affect their development and reproduction (CABALLERO-GALLARDO; OLIVERO-VERBEL; STASHENKO, 2011, CHAUBEY, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for example, in kidney beans, Silva et al (2008) found that Croton grewioides Baill essential oil had a fumigant effect on adults of Z. subfasciatus, Brito et al (2015) observed that C. pulegiodorus and Croton heliotropiifolius Kunth essential oils caused 100% mortality in adults of Z. subfasciatus at all concentrations evaluated (5, 10, 15 and 20 µL L -1 air), in addition to having a repellent effect on insects; Carvalho et al (2016) observed toxicity (fumigant effect) of Croton urucurana Baill essential oil on C. maculatus, causing mortality rates greater than 80% and effects on the biology and survival of this beetle. Similarly, in maize, Magalhães et al (2015) reported that C. pulegiodorus and C. heliotropiifolius essential oils had a repellent effect and caused zero emergence of T. castaneum, while Souza et al (2016) observed that C. pulegiodorus essential oil caused mortality rates above 70% in R. dominica, when used at higher concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…The worldwide-distributed genus Croton L. (Euphorbiaceae), in turn, has proven promising for the management of insect pests of stored products (PEREZ-AMADOR et al, 2007). In Brazil, where research on insects that mainly attack beans and cereals has made important progress in recent years, it is worth mentioning the studies analyzing the effect of essential oils from various Croton species on Callosobruchus maculatus Fabricius and Zabrotes subfasciatus Bohemann (Chrysomelidae) (BRITO et al, 2015;CARVALHO et al, 2016), Tribolium castaneum Herbst (Tenebrionidae) (MAGALHÃES et al, 2015), and Rhyzopertha dominica Fabricius (Bostrichidae) (SOUZA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%